Coumarins, furocoumarins and limonoids of Citrus trifoliata and their effects on human colon adenocarcinoma cell lines. Issue 9 (September 2022) - Kerekes, Diána; Horváth, Attila; Kúsz, Norbert; Borcsa, Botond Lajos; Szemerédi, Nikoletta; Spengler, Gabriella; Csupor, Dezső
Abstract: Citrus trifoliata L. (Chinese or Japanese bitter orange) is a medicinal plant with furocoumarins and limonoids as characteristic secondary metabolites. The bitter taste of the fruit limits its use as food, however, it is applied in Asian traditional medicine for its antiphlogistic effect, to treat digestive ulcers and different gastrointestinal disorders and cancer. The phytochemical composition and pharmacological characteristics of this species have not been fully discovered, nevertheless its potential antiproliferative or cytotoxic effects might be related to furocoumarins or limonoids. Our aim was to isolate and identify secondary metabolites from C. trifoliata peel and seeds and to investigate their bioactivities that might be related to the supposed anticancer effect of the plant. By using different chromatographic methods, six pure compounds (phellopterin (2), scoparone (3 ), myrsellin (4 ), triphasiol (6 ), umbelliferone (7 ) and citropten (5, 7-dimethoxycoumarin (8 )) were isolated from the peel and four (imperatorin (1 ), auraptene (5 ), limonin (9 ) and deacetyl nomilin (10 )) from the seeds of C. trifoliata fruits. These compounds are furocoumarin (1, 2 ), coumarin (3 –8 ), and limonoid derivatives (9, 10 ). Scoparone (3 ) has been detected in this species for the first time. The furocoumarins (1–2 ) showed moderate activity on the human colorectal adenocarcinona tumor cell line COLO 320 in antiproliferative assays and 2 also had remarkable P-glycoprotein inhibitory activity and synergistic effect with doxorubicin. The coumarin 5 showed significant activity on the COLO 320 cell line in antiproliferative assays and P-glycoprotein inhibitory activity in the FACS (fluorescence activated cell sorting) assay. Abstract : Citrus trifoliata, Furocoumarin, Coumarin, Limonoid, Antiproliferative, Synergistic.